Multimodal neuromarkers in schizophrenia via cognition-guided MRI fusion - Jing Sui (Nature Portfolio, 2018)
Cognitive impairment is a feature of many psychiatric diseases. Here the authors aimed to identify multimodal neuromarkers that can be used to quantify and predict cognitive performance in individuals with schizophrenia using three different features of MRI and three independent cohorts.